Autologous Platelet-Rich Plasma Concentrate as an Adjunct to Autologous Retinal Transplant for Large Post-Traumatic Macular Holes Results in Favorable Anatomical and Visual Outcomes: A Case Report - Okonkwo, Ogugua Ndubuisi; Taylor, Alice Cecilia Elsie; Hassan, Adekunle Olubola; Oyekunle, Idris; Oshunkoya, Lateefat; Ishola, Adewale (Archives of Clinical and Medical Case Reports, 2026)
Purpose: Report spontaneous closure of residual eccentric defect following autologous retinal transplant (ART) and adjunct autologous platelet-rich plasma concentrate (PRPC) for a large post-traumatic macular hole (MH), with an unusual improvement in vision after silicone oil removal (SOR). Case description: A 14-year-old male of African descent suffered OD blunt trauma from a projectile, resulting in a large (1200 microns) fullthickness MH. He underwent vitrectomy and ART. At the end of surgery, after fluid-air exchange, three drops of PRPC were added to the ART before silicone oil injection. He had silicone oil removed four weeks postoperation with an air-filled vitreous cavity. Outcome: A notable host–donor eccentric edge defect was observed on OCT day one after ART surgery. The defect was expected to widen with postoperative graft retraction. However, the defect closed spontaneously, seen on OCT one week after surgery. Additionally, two months after SOR, vision improved significantly from 6/36 (20/120) to 6/12 (20/40), N10 unaided. He remains phakic, and no side effects from PRPC were observed. OCT Angiography showed vascularization of the donor graft. Conclusion: This report on ART with adjunctive PRPC shows a positive outcome. We believe PRPC significantly contributed to the uncommon closure of the eccentric defect and the good visual results. Further research on PRPC is needed to explore its potential cellular rejuvenation and fibrin effects in ART, which might result in it becoming standard practice. Larger prospective studies that combine ART and PRPC could provide stronger evidence to validate this method.